The Proposed Dashboard Model for Measuring Performance of Small-Medium Enterprises (SME) - Immawan, Taufiq; Pratiwi, Annisa Indah; Cahyo, Winda Nur (International Journal of Integrated Engineering, 2019)
The era of free market and the more dynamic environment condition forces many companies to establish the proper strategy. Implementation of a correct strategy can increase the effectiveness and efficiency of the use of the company resources. The system of measuring performance is one of models used to monitor the success of implementing objective strategy which has been determined by the leader of the company, including SME (small- medium enterprise). However, a lot of SME do not have clear vision and strategy. It is because the SME orientation only focuses on more dominant operational performance. Therefore, smart system can be used to arrange a parameter of performance measurement. AHP (Analytic Hierarchy Process) is used to determine the priority from each criterion from KPI (Key Performance Indicator). Knowing the proper need, the company can determine the priority to select if the company has limited fund and resources. Moreover, the assessment system used in this research uses OMAX (Objective Matrix) method for each KPI. To assess, the measurement uses the concept of traffic light system using 3 colors: green (achieving a target), yellow (close with the target), and red (far from target). Nevertheless, this KPI needs to get attention in the next period. The research observes 3 SMEs located in Krebet tourism village. They are SME Ragil Handicraft, SME Sanggar Punokawan and SME Yuan art. The result shows that there are 31 keys performance indicators (KPI) used to measure the performance of SME. The assessment result of OMAX shows that there are still a lot of KPIs with red color. Thus, they need to be repaired. Knowing the performance of SME still far from target (red), the sources of the problem can be identified, so that the reparation target done by SME is more appropriate.